The Implementation of a SLiMS-Based Library Automation System Towards the Improvement of Library Quality at FMIPA UNM Makassar - Mustikawati, Mustikawati; Iskandar, Iskandar; Ismail Ahmad, La Ode (Pascasarjana UIN Alauddin Makassar, 2023)
This research aims to find out 1) The Implementation of the SLiMS automation management system in the Makassar State University FMIPA library, 2) Quality improvement with the SLiMS automation system in the Makassar State University FMIPA library and 3) advantages and disadvantages with the SLIMS automation system in the Makassar State University FMIPA library. This research uses descriptive qualitative research while the research approach used is field research. The data sources are from the head of the library and library staff as well as visitors to the FMIPA UNM Library. The data collection methods used in this research are observation, interviews and documentation. The research instrument in this research is the researcher himself. Then the data processing and analysis techniques are carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of this research indicate that the implementation of the automation management system in the Makassar State University FMIPA Library uses the Open Source Senayan Library Management System (SLiMS) automation system. The SLiMS automation system is supported by hardware and software so that the system can run. The hardware used is generally the same, a collection of computers connected to a network, the difference is the software used in the library automation system. The Library quality by using the SLiMS automation system is way better. Users find it easier to use the system, its services, and to obtain information on the books they are seeking. In addition, the automation system of the Open Source Senayan Library Management System (SLIMS) has the benefit of facilitating readers' search for information about wanted books as well as librarians' and staff's ability to finish tasks in the library. The downside is that users are unable to access information remotely because the program is still offline.